Improving Delivery Lead Time In Medical Device Supplies To Public Hospitals In Malaysia - Ramachandram, Kamaleswaran (2015)
This project paper focuses on issues affecting Thera Medic on its delivery lead time for supplies of medical devices (surgical products) to public hospitals in Malaysia. This paper also aims to provide recommendation to improve the overall lead time to meet the lead time expected by the customers.